Secret - Hierro, José Luis del (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The concept of secret is conceived by this work as the exception –necessary– to the publicity and the transparency that, as general norm, are imposed as essential principles of democratic systems. There would be, according to the author, specific occasions in which one of them should give in favor of the protection of juridical goods which need secret, been this official or state secret or regarding judicial actions. This first seeks to protect this information or matter which public acknowledgement would danger the security and the defense of the State. The second one would prohibit the access to disciplinary actions or the publications of its results. The author does a critical analysis of the regulation of our country of both sorts of secrets.
Keywords: Principle of publicity; transparency; official or state secret; secret indictment; professional secret